Microbiological and filth assessment of muscovado marketed by Panay Fair Trade Center - Panugan, Jaycel L. (2009.)
A study was conducted to assess the quality and safety of muscovado produced from three mills affiliated to Panay Fair Trade Center (PFTC).
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Muscovado